2024
DOI: 10.3390/jcm13030799
|View full text |Cite
|
Sign up to set email alerts
|

Circuit Training Improves the Levels of β-Amyloid and Brain-Derived Neurotrophic Factor Related to Cognitive Impairment Risk Factors in Obese Elderly Korean Women

Duwang Kang,
Suhan Koh,
Taekyu Kim
et al.

Abstract: Background: The purpose of this study was to investigate the effect of circuit training on β-amyloid, BDNF, and cognitive function in untrained obese elderly Korean women. Methods: The subjects for the study were aged 65–70 years and were each assigned to a circuit training group (EG, n = 12) or a control group (CG, n = 11). The 60 min combined exercise was performed 3 times per week for 16 weeks. The exercise intensity was progressively increased from a 40% heart rate reserve to a 70% heart rate reserve. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…However, subgroup analyses demonstrated that in APOE-ε4 allele carriers with AD, an increase in CSF Aβ40 was observed in inactive controls after 16 weeks of follow-up while the carriers from the exercise group maintained their baseline concentrations ( 19 ). Other interventions specifically conducted in older women reported that 12 to 16 weeks of resistance exercise training induced a significant reduction in blood Aβ42 concentrations in obese ( 23 ) or pre-diabetic ( 24 ) individuals, compared to inactive groups. Such changes were accompanied by significant reductions in glycated haemoglobin ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, subgroup analyses demonstrated that in APOE-ε4 allele carriers with AD, an increase in CSF Aβ40 was observed in inactive controls after 16 weeks of follow-up while the carriers from the exercise group maintained their baseline concentrations ( 19 ). Other interventions specifically conducted in older women reported that 12 to 16 weeks of resistance exercise training induced a significant reduction in blood Aβ42 concentrations in obese ( 23 ) or pre-diabetic ( 24 ) individuals, compared to inactive groups. Such changes were accompanied by significant reductions in glycated haemoglobin ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the studies included in this short review demonstrated no effect of exercise interventions on the main biomarkers of AD, which is in line with previous reviews on the topic ( 31 , 32 ). Nonetheless, some factors such as sex, APOE genotype or health status, seem to modify the effect of exercise training, as favourable and significant findings regarding Aβ levels were reported in women with obesity ( 23 ), pre-diabetes ( 24 ), or depression ( 25 ) and in APOE-ε4 carriers individuals with AD ( 19 ). Hence, it is possible that exercise still has an effect on specific populations that display risks factors for AD such as women ( 33 ), APOE-ε4 genotype carriers ( 34 ), individuals with metabolic disorders ( 35 ) or depression ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that BDNF levels increase during physical exercise, including a study of cardiac surgery patients [29,49]. It was indicated that mood and cognitive functions improved in elderly patients with various levels of depression who underwent cognitive training, which was accompanied by an increase in the serum concentration of BDNF [50].…”
Section: Discussionmentioning
confidence: 99%